Reliability and validity of the BEARS sleep disorder questionnaire in children and adolescent students from Bogotá, D.C., Colombia: FUPRECOL study (2018)
Sleep plays a vital role in good health and well-being in school-age children. The aim of this study was to determine the reliability and content validity of the BEARS questionnaire in children and adolescents from 9 to 17 years of age. The sample comprised 8,862 children and adolescents belonging to 24 official education institutions from Bogotá, Colombia. The BEARS questionnaire was applied through self-completion manner, with a structured form. A sub-sample of 246 participants was used for reliability analyses. Consistency of the instrument was analyzed through Cronbach’s alpha coefficient, construct validity through exploratory factor analysis (EFA), and reliability through the weighted Kappa coefficient. Results showed adequate consistency (global Cronbach of 0.732; range 0.706 to 0.769) and moderate reliability (Kappa of 0.665; range 0.706 to 0.769). The EFA determined a single factor (item 1: problems when going to sleep), which explained 61.4% of the variance, grouping two interactions ÷2/gl = 2690.817; p = 0.001. The BEARS questionnaire showed adequate internal consistency, reliability, and validity. From these results, this instrument is recommended principally within the context of primary care for the study and screening of sleep alterations in school-aged populations from Bogotá, Colombia. © Copyright: Federación Española de Asociaciones de Docentes de Educación Física (FEADEF)